Negative consequences associated with dependence in daily cannabis users - Earleywine Mitch; Looby Alison (BMC, 2007)
Abstract Background Cannabis is the most widely consumed illicit substance in America, with increasing rates of use. Some theorists tend to link frequency of use with cannabis dependence. Nevertheless, fewer than half of daily cannabis users meet DSM-IV-TR criteria for cannabis dependence. This study seeks to determine whether the negative aspects associated with cannabis use can be explained by a proxy measure of dependence instead of by frequency of use. Results Over 2500 adult daily cannabis users completed an Internet survey consisting of measures of cannabis and other drug use, in addition to measures of commonly reported negative problems resulting from cannabis use. We compared those who met a proxy measure of DSM-IV-TR criteria for cannabis dependence (N = 1111) to those who did not meet the criteria (N = 1770). Cannabis dependent subjects consumed greater amounts of cannabis, alcohol, and a variety of other drugs. They also had lower levels of motivation, happiness, and satisfaction with life, with higher levels of depression and respiratory symptoms. Conclusion Although all of our subjects reported daily use, only those meeting proxy criteria for cannabis dependence reported significant associated problems. Our data suggest that dependence need not arise from daily use, but consuming larger amounts of cannabis and other drugs undoubtedly increases problems.